Pracownia Digitalizacji Zbiorów Wojewódzkiej i Miejskiej Biblioteki Publicznej w Rzeszowie - Rak, Agata; Zajdel, Michał (My University, 2015)
Artykuł przedstawia proces powstania i rozwoju Pracowni Digitalizacji Zbiorów Wojewódzkiej i Miejskiej Biblioteki Publicznej w Rzeszowie z wykorzystaniem funduszy unijnych. Omówiono cele i zadania Pracowni, scharakteryzowano warunki lokalowe, wyposażenie oraz zastosowane rozwiązania informatyczne, a także nakreślono plany rozwoju. Pracownia Digitalizacji Zbiorów WiMBP w Rzeszowie kompleksowo rozwija usługi i zasoby cyfrowe m. in. w ramach takich projektów jak: Podkarpacka Biblioteka Cyfrowa oraz E-usługi w nowoczesnej bibliotece.

The article presents the process of creation and development of the Digitisation Studio of the Collection of the Provincial and City Public Library in Rzeszow by using the European Union funds. In this piece of writing the readers can find information about the aims and tasks of the Digitisation Studio of the Collection and the description of the housing conditions. In addition, the equipment and the application of IT solutions are included in this article; there is also an outline of the development plan. It is necessary to mention that Digitisation Studio of the Collection of the Provincial and City Public Library in Rzeszow provides services and digital resources within the projects such as the Subcarpathian Digital Library and E-services in the modern library.
Laboratory Digitisation Collections Provincial and City Public Library in Rzeszow
Keywords: Pracownia Digitalizacji Zbiorów; Wojewódzka i Miejska Biblioteka Publiczna w Rzeszowie; digitalizacja; nowoczesne technologie; skanery; rozwiązania informatyczne; Podkarpacka Biblioteka Cyfrowa; E-usługi w nowoczesnej bibliotece; The Digitisation Studio of the Collection; The Provincial and City Public Library in Rzeszow; digitisation; modern technologies; IT solutions, scanners; The Subcarpathian Digital Library; E-service in the modern library